2003
DOI: 10.1080/gye.17.1.57.63
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of finasteride for hirsute women with polycystic ovary syndrome or idiopathic hirsutism

Abstract: Finasteride has been used frequently in the treatment of prostate hyperplasia, but this drug inhibits 5alpha-reductase and for this reason could be useful for the treatment of hirsutism. The aim of this study was to evaluate the clinical and hormonal effects of finasteride on hirsute women with idiopathic hirsutism or polycystic ovary syndrome. Twenty-four women were randomly divided into two groups: those given placebo and those given finasteride 5 mg/day. The treatment period was 6 months. All patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 32 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…5 Finasteride is a 5 alpha-reductase inhibitor that may be effective for the treatment of hirsute woman with idiopathic hirsutism or polycystic ovary syndrome. 6 Thus, an excess of skin 5 alphareductase activity may be considered a cause of hirsutism. 7 Green tea, which is widely consumed in China, Japan, and India, contains polyphenolic compounds that account for 30% of the dry weight of the leaves.…”
Section: Dear Editormentioning
confidence: 99%
“…5 Finasteride is a 5 alpha-reductase inhibitor that may be effective for the treatment of hirsute woman with idiopathic hirsutism or polycystic ovary syndrome. 6 Thus, an excess of skin 5 alphareductase activity may be considered a cause of hirsutism. 7 Green tea, which is widely consumed in China, Japan, and India, contains polyphenolic compounds that account for 30% of the dry weight of the leaves.…”
Section: Dear Editormentioning
confidence: 99%
“…Four studies, three of which were RCTs, demonstrated a significant decrease in Ferriman-Gallwey (FG) score after 6-12 months of oral finasteride for treatment of idiopathic hirsutism (IH) or hirsutism secondary to PCOS. 43,44,55,64 Another study showed both finasteride (5 mg/day) alone and finasteride with an oral contraceptive to significantly improve hirsutism after 6 months, but only combination therapy showed significant reduction in DHT. 65 There are several prospective studies by Bayram et al on oral finasteride treatment in hirsute women.…”
Section: Acnementioning
confidence: 99%
“…Significant anti-androgenic effects were shown after 6 months of treatment at 5 mg/day dose [20,21]. The use of 5α-reductase inhibition therapy should be considered when the previous therapy with oral contraceptive and spironolactone is relatively ineffective [22].…”
Section: Treatment Options For Women With Hyperandrogenismmentioning
confidence: 99%
“…A3 0 -35 day cycle can also be anovulatory. Measurement of serum progesterone in the midluteal stage (Days [21][22] is the best way to evaluate ovulation. Progesterone levels > 2.5 ng/mL may indicate ovulation but values of ≥7 ng/mL are needed for normal luteal function [7].…”
Section: Detecting Of Ovulatory Dysfunctionmentioning
confidence: 99%